2018
DOI: 10.1038/s41467-018-04218-4
|View full text |Cite
|
Sign up to set email alerts
|

Macroecology and macroevolution of the latitudinal diversity gradient in ants

Abstract: The latitudinal diversity gradient—the tendency for more species to occur toward the equator—is the dominant pattern of life on Earth, yet the mechanisms responsible for it remain largely unexplained. Recently, the analysis of global data has led to advances in understanding, but these advances have been mostly limited to vertebrates and trees and have not provided consensus answers. Here we synthesize large-scale geographic, phylogenetic, and fossil data for an exemplar invertebrate group—ants—and investigate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

13
163
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 171 publications
(177 citation statements)
references
References 68 publications
13
163
1
Order By: Relevance
“…These results for Pheidole evolution in the post‐Oligocene connect well to results on ant diversification on deeper time‐scales (Economo et al, ), and together tell a coherent story about the evolution of latitudinal gradients in ants across scales. Most ant lineages older than 34 Ma are reconstructed to be tropical, including the Pheidole stem lineage.…”
Section: Discussionsupporting
confidence: 81%
See 2 more Smart Citations
“…These results for Pheidole evolution in the post‐Oligocene connect well to results on ant diversification on deeper time‐scales (Economo et al, ), and together tell a coherent story about the evolution of latitudinal gradients in ants across scales. Most ant lineages older than 34 Ma are reconstructed to be tropical, including the Pheidole stem lineage.…”
Section: Discussionsupporting
confidence: 81%
“…Once colonization of cold biomes occurred, diversification was not detectably slower. In their analysis across all ant clades, Economo et al () also found no evidence for elevated net diversification rates among clades centred in the tropics relative to those in the temperate zone, although clades are quite heterogeneous in rate, probably due to other latent biological and historical differences. It remained possible that diversification rate was correlated with latitude within the large clades, but biological differences among clades obscured this pattern.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…According to this hypothesis, we can expect the number of species per higher taxon in random samples to increase from the poles to the equator and, potentially, from mountain tops to mountain bases. Although the diversification rate hypothesis has not been supported by recent studies of ants (Economo, Narula, Friedman, Weiser, & Guénard, ) and marine fishes (Rabosky et al, ), an increasing trend in the species : family ratio from high to low latitude has been observed for eastern Pacific marine molluscs (Roy, Jablonski, & Valentine, ). The high heterogeneity of environmental conditions linked, for example, to mountainous environments and precipitation gradients in many terrestrial systems might limit the strength of this trend in terrestrial taxa (McClain, White, & Hurlbert, ; Rundell & Price, ).…”
Section: Introductionmentioning
confidence: 94%
“…One of these concepts examines spatial patterns of biodiversity loss of specific taxa (e.g., amphibians, reptiles, and spiders) and their drivers ("Concept 19"; Figure 6) and is used across a range of both basic and applied subdisciplines, such as ecology, microbiology, molecular biology, and agriculture. Since 2012, the publication of comprehensive, open data sets containing the spatial and temporal distribution of species from multiple taxa such as ants, birds, plants, and reef fishes (Bruelheide et al, 2018;Dornelas et al, 2018;Economo, Narula, Friedman, Weiser, & Guénard, 2018;Edgar & Stuart-Smith, 2014;Jetz, Thomas, Joy, Hartmann, & Mooers, 2012) may have altered the trajectory of interdisciplinarity for this concept. Research on this concept may have become concentrated among an increasingly smaller number of subdisciplines in biodiversity science given its restricted taxonomic scope.…”
Section: Our Analysis Identified a Number Of Concrete Examples Wherementioning
confidence: 99%